2008
DOI: 10.1038/gene.2008.67
|View full text |Cite
|
Sign up to set email alerts
|

A T-cell-specific CD154 transcriptional enhancer located just upstream of the promoter

Abstract: CD154 (CD40-ligand) is a critical immune regulator. CD154 expression is tightly regulated and largely restricted to activated CD4 T cells. Using DNase I hypersensitivity site (HSS) mapping, we identified two novel HSS mapping to the human CD154 promoter element and just upstream. Both HSS were activation independent and CD4 T-cell specific. Approximately 350 bp of DNA sequence flanking the upstream HSS site was highly conserved between mouse and man, and was rich in binding sites for GATA and NFAT proteins. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…We found that CD40L expression is tightly regulated by STIM1 and STIM2, since DKO CD4 + T cells have strongly reduced levels of CD40L at their cell surface before and after activation. Regulation of CD40L by STIM1 and STIM2 is consistent with the role of the Ca 2+ -dependent transcription factor NFAT in CD40L expression in murine and human T cells (72)(73)(74) and inhibition of de novo expression of CD40L by cyclosporine A, a calcineurin inhibitor (75). The important role of STIM1 and STIM2 in CD40L-dependent CD4 + T cell help for memory CD8 + T cell responses to LCMV is supported by the reduced numbers of memory CD8 + T cells in DKO:Cd40l -/-compared with WT:Cd40l -/-chimeras and the reduced MHC class II expression levels on DCs isolated from DKO mice, indicating that STIM1/2-dependent CD40L expression is required for DC licensing.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We found that CD40L expression is tightly regulated by STIM1 and STIM2, since DKO CD4 + T cells have strongly reduced levels of CD40L at their cell surface before and after activation. Regulation of CD40L by STIM1 and STIM2 is consistent with the role of the Ca 2+ -dependent transcription factor NFAT in CD40L expression in murine and human T cells (72)(73)(74) and inhibition of de novo expression of CD40L by cyclosporine A, a calcineurin inhibitor (75). The important role of STIM1 and STIM2 in CD40L-dependent CD4 + T cell help for memory CD8 + T cell responses to LCMV is supported by the reduced numbers of memory CD8 + T cells in DKO:Cd40l -/-compared with WT:Cd40l -/-chimeras and the reduced MHC class II expression levels on DCs isolated from DKO mice, indicating that STIM1/2-dependent CD40L expression is required for DC licensing.…”
Section: Discussionmentioning
confidence: 54%
“…Briefly, splenocytes were isolated from LCMV ARM -infected mice at day 8 p.i. and either left untreated or stimulated with LCMV GP [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] peptide (30 μg/ml) or PMA (20 nM) plus ionomycin (1 μM) for 2 hours at 37°C in the presence of 1 μg/ml anti-CD40L antibody (clone MR1; eBioscience) to capture CD40L at the cell surface. Cells were washed, stained with additional antibodies against surface markers as indi-…”
Section: Micementioning
confidence: 99%
“…Since CD154 exerts pleiotropic effects on a wide variety of CD40-expressing cells making significant impacts on immune regulation, its expression should be tightly regulated. The expression of CD154 has been shown to be controlled at both transcriptional and post-transcriptional level, although its regulation mechanisms have still remained to be thoroughly defined [50,51]. Especially, few transcription factors that repress CD154 expression have so far been identified.…”
Section: Discussionmentioning
confidence: 98%
“…Murine sequences are highly (75%) homologous with the human DNA in the 3' enhancer region, however none of the eleven CG pairs in the human gene in this region were present in mice, so no further examination of this region was performed. After our initial report on methylation of the human CD40LG regulatory sequences, a second enhancer approximately 5' of the TSS in humans was reported [58] in a region highly homologous between mice and humans. These sequences may be important regulatory regions for future study.…”
Section: Discussionmentioning
confidence: 99%